Online monitoring applying the anaerobic respiratory monitoring system reveals iron(II) limitation in YTF medium for Clostridium ljungdahlii. Issue 1 (5th November 2020) - Mann, Marcel; Wittke, Darina; Büchs, Jochen
Abstract: Online monitoring of microbial cultures is an effective approach for studying both aerobic and anaerobic microorganisms. Especially in small‐scale cultivations, several parallel online monitored experiments can generate a detailed understanding of the cultivation, compared to a situation where a few data points are generated from time course sampling and offline analysis. However, the availability of small‐scale online monitoring devices for acetogenic organisms is limited. In this study, the previously reported anaerobic Respiration Activity MOnitoring System (anaRAMOS) device was adapted for online monitoring of Clostridium ljungdahlii ( C. ljungdahlii ) cultures with fructose as the carbon source. The anaRAMOS was applied to identify conversion of different carbon sources present in commonly used YTF medium. An iron(II) deficiency was discovered in this medium for C. ljungdahlii . Addition of iron(II) to the YTF medium reduced the cultivation time and increased biomass yield of C. ljungdahlii cultures by 50% and 40%, respectively. The measurement of the carbon dioxide transfer rate was used to calculated the iron(II) contained in complex components. By demonstrating the application of the anaRAMOS device for medium optimization, it is proven that the described online monitoring device has potential for use in process development.